2017
DOI: 10.2141/jpsa.0170004
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and Glucagon Stimulate Gene Expression of Pyruvate Dehydrogenase Kinase 4 in Chickens

Abstract: The excessive accumulation of body fat has become a serious problem in the broiler industry. However, the molecular mechanisms underlying the regulation of lipid metabolism-related genes in broiler chickens are not fully understood. In the present study, we investigated the role of glucagon on the expression of lipid metabolism-related genes in chicken white adipose tissue (WAT). Four hours of fasting significantly increased plasma levels of free fatty acid in broiler chickens. The mRNA levels of adipose trigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…For example, no homolog of the HSL gene has been identified in the chicken genome, although an HSL-like enzyme has been purified from chicken WAT (Anthonsen et al 1997). However, we found that 4 h of fasting significantly increased mRNA levels of ATGL and reduced mRNA levels of LPL in chicken WAT (Saneyasu et al 2013b;Honda et al 2017). We also showed that plasma NEFA concentrations were significantly elevated after 4 h of fasting (Honda et al 2017).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, no homolog of the HSL gene has been identified in the chicken genome, although an HSL-like enzyme has been purified from chicken WAT (Anthonsen et al 1997). However, we found that 4 h of fasting significantly increased mRNA levels of ATGL and reduced mRNA levels of LPL in chicken WAT (Saneyasu et al 2013b;Honda et al 2017). We also showed that plasma NEFA concentrations were significantly elevated after 4 h of fasting (Honda et al 2017).…”
Section: Introductionmentioning
confidence: 67%
“…However, we found that 4 h of fasting significantly increased mRNA levels of ATGL and reduced mRNA levels of LPL in chicken WAT (Saneyasu et al 2013b;Honda et al 2017). We also showed that plasma NEFA concentrations were significantly elevated after 4 h of fasting (Honda et al 2017). Therefore, transcriptional regulation of LPL and ATGL may play important roles in the regulation of body fat accumulation in chickens.…”
Section: Introductionmentioning
confidence: 77%
“…The starvation process is also associated with the stimulation of metabolic processes related to the release of stored energy substances, e.g., in the form of nonesterified fatty acids (NEFA), which result from the intensification of lipolytic processes as well as activation of genes involved in lipid metabolism in fat tissue and liver [ 26 , 27 ]. PDK4 is considered to be involved in re-esterification of fatty acid derived from lipolysis during fasting.…”
Section: Discussionmentioning
confidence: 99%
“…PDK4 is considered to be involved in re-esterification of fatty acid derived from lipolysis during fasting. [ 26 , 28 ]. Previous studies performed on mammals showed that SPX is able to regulate both of these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Severe feed restriction in the first weeks of life of chickens promotes protein catabolism associated with elevated levels of uric acid in plasma, due to the process of gluconeogenesis from amino acids and glycerol in the liver (Jahanpour et al, 2013). This process is regulated by the predominance of the effects of glucagon on insulin in response to fasting (Christensen et al, 2013), which also leads to lipolysis for the production of glycerol for the gluconeogenesis process (Honda et al, 2017). In this study, birds exposed to prolonged fasting (48 and 72 h) had allometric growth values of the viscera (gizzard, proventriculus, liver and intestine) superior to 1 at three days of life, which probably can be explained by the degradation of body protein and its use as a source of energy for the maintenance of body homeostasis.…”
Section: Discussionmentioning
confidence: 99%